Birthweight and isolated congenital heart defects – A systematic review and meta‐analysis. (15th April 2022) - Aliasi, Moska; Snoep, Maartje C.; van Geloven, Nan; Haak, Monique C.
Abstract: Background: Birthweight (BW) is an important prognostic factor in newborns with congenital heart defects (CHD). Objectives: To give an overview of the literature on BW z ‐score in children with isolated CHD. Search strategy: A systematic search was performed on isolated CHD and BW in PubMed, Embase, Web of Science, COCHRANE Library and Emcare. Selection criteria: Neonates with isolated CHD were included if a BW percentile, BW z ‐score or % small‐or‐gestational age (SGA) was reported. Data collection and analysis: BW z ‐score and percentage SGA were pooled with random‐effect meta‐analysis. Quality and risk of bias were assessed using the modified Newcastle Ottawa Scale. Main results: Twenty‐three articles (27 893 cases) were included. BW z ‐scores were retrieved from 11 articles, resulting in a pooled z ‐score of −0.20 (95% CI −0.50 to 0.11). The overall pooled prevalence of SGA <10th percentile was 16.0% (95% CI 11.4–20.5; 14 studies). Subgroup analysis of major CHD showed similar results (BW z ‐score −0.23 and percentage SGA 16.2%). Conclusions: Overall BW in isolated CHD is within range of normality but impaired, with a 1.6‐fold higher risk of SGA, irrespective of the type of CHD (major CHD vs all CHD combined). Our findings underline the association between CHD and BW. The use of BW z ‐scores provides insight into growth of all fetuses with CHD. Tweetable abstract: Infants with a congenital heart defect (CHD) have a lower birthweight z ‐score and a higher incidence of small‐for‐gestational age (<10th percentile). This was encountered both in the major CHD‐group as well as in all‐CHD combined group analysis. Future research on the association between birthweight and CHD should include all types of CHDs (including mild cardiac defects) and placental‐related disease, such as pre‐eclampsia. We advocate the use of international standardised fetal growth and birthweight charts in CHD research. Tweetable abstract: Infants with a congenital heart defect (CHD) have a lower birthweight z ‐score and a higher incidence of small‐for‐gestational age (<10th percentile). This was encountered both in the major CHD‐group as well as in all‐CHD combined group analysis. Future research on the association between birthweight and CHD should include all types of CHDs (including mild cardiac defects) and placental‐related disease, such as pre‐eclampsia. We advocate the use of international standardised fetal growth and birthweight charts in CHD research.